2017
DOI: 10.5543/tkda.2017.57034
|View full text |Cite
|
Sign up to set email alerts
|

The approach to aortic aneurysms in the elderly

Abstract: There is an increase in the number of older persons worldwide. Because of this in the future we will much more manage the diseases which are more commonly seen in elderly in daily practice. One of the mortal diseases commonly seen in elderly patients is aortic aneurysm. Aort aneurysms are vary rare in patients under 50 age. When a patient over 65 age is examined, aortic aneurysm should take place in differential diagnosis list. aneurysm may be seen at both thoracic and abdominal aorta, but abdominal aorta is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…[ 4 , 5 ] At present, some progress has been made in the research of TAA in genetics, proteomics, hemodynamics, and treatment methods; however, there is still a high mortality rate, and there is no clinically feasible method to prevent the occurrence of aortic aneurysm. [ 6 , 7 ] Therefore, early diagnosis and identification of TAAs are important.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 , 5 ] At present, some progress has been made in the research of TAA in genetics, proteomics, hemodynamics, and treatment methods; however, there is still a high mortality rate, and there is no clinically feasible method to prevent the occurrence of aortic aneurysm. [ 6 , 7 ] Therefore, early diagnosis and identification of TAAs are important.…”
Section: Introductionmentioning
confidence: 99%
“…This process usually occurs in later decades, at about the age of 60 or 70 years. Smoking and hypertension are also associated with aneurysm development 3 . Inflammatory diseases of the aorta can be classified as a spectrum of diseases with different clinical and histopathological definitions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Based on previous studies, the causes of TAA include atherosclerosis, hypertension, infection, immune system diseases, and vascular wall lesions. 4 Recent studies have shown that multiple inflammation-related factors are closely associated with the pathogenesis of TAAs. 5,6 The main pathological manifestations of TAA are continuous dilation of the artery caused by the invasion of inflammatory cells, destruction of the middle elastic protein matrix, inflammatory cell infiltration in the aortic wall, thrombosis in the lumen, and elevated C-reactive protein (CRP) levels.…”
Section: Introductionmentioning
confidence: 99%